2018
DOI: 10.1038/s41598-018-34960-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemically modified hCFTR mRNAs recuperate lung function in a mouse model of cystic fibrosis

Abstract: Gene therapy has always been a promising therapeutic approach for Cystic Fibrosis (CF). However, numerous trials using DNA or viral vectors encoding the correct protein resulted in a general low efficacy. In the last years, chemically modified messenger RNA (cmRNA) has been proven to be a highly potent, pulmonary drug. Consequently, we first explored the expression, function and immunogenicity of human (h)CFTR encoded by cmRNAhCFTR in vitro and ex vivo, quantified the expression by flow cytometry, determined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 55 publications
0
54
0
1
Order By: Relevance
“…A significant decrease in chloride concentration (around 50%) was also observed, indicating a restoration of CFTR in the duct compartment of submucosal glands and thus leading to improved chloride absorption. 20 A separate study from Robinson et al 181 confirmed nasal application of chemically modified CFTR mRNA can recover up to 55% of the net chloride efflux characteristic of healthy mice. Bangel-Ruland et al 182 demonstrate restoration of cAMP-induced CFTR current following transfection of CFBE41ocells with wild-type CFTR-mRNA similar to the values seen in 16HBE14o-control cells.…”
Section: Asthmamentioning
confidence: 96%
See 4 more Smart Citations
“…A significant decrease in chloride concentration (around 50%) was also observed, indicating a restoration of CFTR in the duct compartment of submucosal glands and thus leading to improved chloride absorption. 20 A separate study from Robinson et al 181 confirmed nasal application of chemically modified CFTR mRNA can recover up to 55% of the net chloride efflux characteristic of healthy mice. Bangel-Ruland et al 182 demonstrate restoration of cAMP-induced CFTR current following transfection of CFBE41ocells with wild-type CFTR-mRNA similar to the values seen in 16HBE14o-control cells.…”
Section: Asthmamentioning
confidence: 96%
“…178 Similarly, DNA-based vectors (viral and plasmid) were tested by Alton's group (pGM169/GL67A), reaching phase II clinical trials with modest improvement in FEV 1 after repeated administration but no improvement in patient's quality of life. 179,180 Haque et al 20 have observed a significant improvement in CFTR protein translation, expression, and function in vitro (CFBE41o-and 16HBE14o-) and in vivo (CFTR-knockout mice) by administering chemically modified human CFTR (hCFTR) mRNAs complexed with chitosan-coated poly(lactic-co-glycolic acid) (PLGA) nanoparticles. The study also showed a substantial improvement in FEV 0.1 up to 89% of the level of a healthy control group.…”
Section: Asthmamentioning
confidence: 99%
See 3 more Smart Citations